1999
DOI: 10.1093/jn/129.3.672
|View full text |Cite
|
Sign up to set email alerts
|

Women's Dietary Intakes in the Context of Household Food Insecurity

Abstract: A study of food insecurity and nutritional adequacy was conducted with a sample of 153 women in families receiving emergency food assistance in Toronto, Canada. Contemporaneous data on dietary intake and household food security over the past 30 d were available for 145 of the women. Analyses of these data revealed that women who reported hunger in their households during the past 30 d also reported systematically lower intakes of energy and a number of nutrients. The effect of household-level hunger on intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
129
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(143 citation statements)
references
References 28 publications
9
129
1
4
Order By: Relevance
“…In our study, whether consumption of higher-energy dense foods in combination with more time spent in physically less vigorous activities (domestic and leisure activities) and physical limitations is associated with household food insecurity and thus contributes to overweight and obesity requires further examination. Several studies have shown that the diets of women reporting household food insecurity or food insufficiency were not only inadequate in nutrient and food variety, but also in calorie (Kendall et al, 1996;Rose & Oliveira, 1997;Tarasuk & Beaton, 1999;Rose, 1999;Dixon et al, 2001). In the present study, none of the energy, nutrient or food group intakes was significantly different among the food-secure and food-insecure groups; however, the food variety score as an indicator of dietary diversity was highest in the foodsecure group than all of the food-insecure groups.…”
Section: Discussioncontrasting
confidence: 71%
“…In our study, whether consumption of higher-energy dense foods in combination with more time spent in physically less vigorous activities (domestic and leisure activities) and physical limitations is associated with household food insecurity and thus contributes to overweight and obesity requires further examination. Several studies have shown that the diets of women reporting household food insecurity or food insufficiency were not only inadequate in nutrient and food variety, but also in calorie (Kendall et al, 1996;Rose & Oliveira, 1997;Tarasuk & Beaton, 1999;Rose, 1999;Dixon et al, 2001). In the present study, none of the energy, nutrient or food group intakes was significantly different among the food-secure and food-insecure groups; however, the food variety score as an indicator of dietary diversity was highest in the foodsecure group than all of the food-insecure groups.…”
Section: Discussioncontrasting
confidence: 71%
“…Energy intakes overall were similar to those reported by mothers the same age in Canada seeking food assistance (34) and in data from the Continuing Survey of Food Intakes of Individuals (12), but 150 to 200 kcal less than those reported by women in a national survey (35) and 400 kcal less than those reported in another regional survey of African-American and white adults in southern states (36). In our study, the energy intakes of the Hispanic women were both significantly higher than those of the other ethnic groups and similar to those from national survey data (8).…”
Section: Discussionsupporting
confidence: 70%
“…Because food insecurity results in shifts or alterations to one's diet in both high income (Rose, 1999;Tarasuk and Beaton, 1999;Dixon et al, 2000;Lee and Frongillo, 2001;Zizza et al, 2008) and low-income settings (MelgarQuinonez et al, 2006;Hadley et al, 2007;Knueppel et al, 2010) many have explored the potential relationship between food insecurity and measures of undernutrition and overnutrition, including overweight and obesity. The results of this work highlight the variation in the relationship between measures of food insecurity and measures of nutritional wellbeing.…”
Section: Food Security and Nutritional Statusmentioning
confidence: 99%